Assessment of the risk of colorectal cancer in Poland on the basis of the analysis of epidemiological indicators - Grażyna R. Wiraszka; Maciej Kielar; Renata B. Stępień (Studia Medyczne, 2015)
Malignant tumours are one of the leading causes of death, as well as one of the most important health problems, in Poland and worldwide. Aim of the research was to assess the risk of colorectal cancer in a population of men and women in Poland based on the analysis of data from the most recent studies and epidemiological sources, particularly from the National Cancer Registry. In this study, epidemiological indicators of incidence and deaths for general colorectal cancer (ICD-10: C18–C21) as well as for particular cancer locations (C18 – colon, C19 – rectosigmoid junction, C20 – rectum, C21 – anus and anal canal) analized in men and women in Poland in 2011 as well as the profile of these parameters in years 1999–2011. The incidence for colorectal cancer (CRC) in man: structure indicators (SI) – 12.4%, age standardized rates (ASR) – 30.2/105; in women: SI – 10.0%, ASR – 18.0/105. The deaths due to CRC in men: SI – 11.4%, ASR – 19.8/105; in women: SI – 11.8%, ASR – 10.2/105. Colorectal cancer is a serious threat to the health of Poles, characterised by its dynamics increasing with population age, by high incidence and mortality, as well as by a persistent, constant tendency for increasing epidemiological rates, especially among men. The differentiation of epidemiological rates follows from tumour location. Higher incidence and mortality rates are registered for the population of men and among the residents of Western Poland.